2012
DOI: 10.1038/nmeth.2210
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticle–mediated massively parallel mechanical modulation of single-cell behavior

Abstract: We report a technique for generating controllable, time-varying and localizable forces on arrays of cells in a massively parallel fashion. To achieve this, we grow magnetic nanoparticle-dosed cells in defined patterns on micro-magnetic substrates. By manipulating and coalescing nanoparticles within cells, we apply localized nanoparticle-mediated forces approaching cellular yield tensions on the cortex of HeLa cells. We observed highly coordinated responses in cellular behavior, including the p21-activated kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
166
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(171 citation statements)
references
References 44 publications
(46 reference statements)
2
166
0
Order By: Relevance
“…Several approaches have been designed for this purpose, e.g., inkjet cell printing (3)(4)(5)(6), surface engineering (7)(8)(9)(10)(11)(12)(13)(14)(15), and physical constraints (16)(17)(18)(19)(20)(21)(22)(23). However, finding a method that completely satisfies the above requirements remains a challenge.…”
mentioning
confidence: 99%
“…Several approaches have been designed for this purpose, e.g., inkjet cell printing (3)(4)(5)(6), surface engineering (7)(8)(9)(10)(11)(12)(13)(14)(15), and physical constraints (16)(17)(18)(19)(20)(21)(22)(23). However, finding a method that completely satisfies the above requirements remains a challenge.…”
mentioning
confidence: 99%
“…Micro-devices patterned with magnetic elements have been fabricated to establish steep magnetic gradients to enhance the magnetization of MNPs and resulting forces on neurons. 53 It has been shown that internalized MNPs can influence the protein tau distribution which affects the polarization of neurites for axon formation. 54 Calcium is an important second messenger that is implicated in various signaling pathways that regulate gene expression.…”
Section: Nano-technology Toolsmentioning
confidence: 99%
“…smallest diameter of the concentrated circle) and 10-20 μm effective length. Note that relocalization of the proteins was induced by force-induced active transport ( Etoc et al, 2013 ;Hoffmann et al, 2013 ;Mannix et al, 2008 ;Tseng et al, 2012 ), rather than by passive diffusion followed by trapping of proteins as in optogenetic methods ( Levskaya et al, 2009 ). This property of MPNs is advantageous for directing the reorganization of confined or slowly diffusing membrane proteins such as Notch and E-cadherin receptors ( Farlow et al, 2013 ).…”
Section: Nanoprobe-mediated Spatial Reorganization and Force-inducedmentioning
confidence: 99%
“…Microprobe-based force microscopy tools can deliver a specific force to purified biomolecules ( Dufrêne et al, 2011 ;Neuman and Nagy, 2008 ), but, due to the large size and multivalent character of microprobes, these tools are not ideal for spatial control of individual membrane proteins in live cells due to their propensity to cluster upon binding (Details in Result sections). Magnetic nanoparticles were previously used for controlling the subcellular distribution of proteins ( Bharde et al, 2013 ;Cho et al, 2012 ;Etoc et al, 2013 ;Hoffmann et al, 2013 ;Mannix et al, 2008 ;Tseng et al, 2012 ), but have not been used for mechanical loading of single biomolecules with controlled force. Therefore, new experimental tools are needed to probe the spatial, temporal, chemical, and mechanical regulation of mechanosensitive membrane proteins in a single and integrated platform.…”
Section: Introductionmentioning
confidence: 99%